Current environmental issues and challenges - Cao, Giacomo; Orru, Roberto (Springer, 2014)
This book's aim is to bring together, in one volume, state-of-the-art information on a number of current environmental issues and challenges. The chapters dealing with air pollution from mobile sources, air pollution and health effects, and air quality modelling fall into the air pollution category. Chapters related to microalgae for carbon dioxide sequestration/biofuels production, fuel cells, and solar energy technology, respectively, can be ascribed to the energy topic. Several technologies to handle a wide spectrum of environmental pollutants are taken into account in the corresponding chapters: self-propagating high-temperature reactions, catabolic plasmids biodegradation, dust removal, glyphosate biodegradation, bioleaching, and probiotic bacteria for water sanitation. The chapter on biodiversity is clearly related to the conservation issue, while the water pollution subject is tackled by the chapter on water quality monitoring. Environmental management is considered with a general analysis on green business, as well as a chapter on using grid/cloud computing technology for collaborative problem solving and shared resources management. Each chapter is stand-alone to allow the user rapid access to the subject of interest.Few books currently exist that cover such a wide spectrum of topics. For this reason it is intended as a text for graduate courses in environmental science and engineering, as well as for reference by researchers and practitioners interested in the latest developments in the environmental field